Dynamic resource scheduling of biomanufacturing projects. (September 2020) - Limon, Yasemin; Krishnamurthy, Ananth
Highlights: Obtaining desired schedules for biomanufacturing projects is a complex problem. We propose a dynamic scheduling approach for effective scheduling of projects. We solve a series of mixed-integer linear programming models to revise schedules. We develop a scheduling tool that incorporates the user feedback in the schedules. We validate our approach with implementation in an industry setting. Abstract: We consider the scheduling problem for biomanufacturing projects that involve multiple tasks and "no-wait" constraints between some of these tasks. The aim is to create schedules that ensure timely delivery of products while enabling schedule revisions to accommodate additional constraints realized during the execution of these projects. We formulate the problem as a mixed-integer linear programming model with the objective of minimizing total tardiness, and propose a dynamic scheduling approach that solves a series of modified mixed-integer linear programming models to revise and improve the schedule. We conduct numerical studies to investigate the performance of this approach and compare its performance to a traditional proactive scheduling approach. In collaboration with biomanufacturing companies, we create a scheduling tool and validate the approach with implementation in an industry setting.